Arsitektur Alif dan Alef: Studi Komparasi Semiotik Ontologi Arab dan Ibrani - Ulil Abshor, Ulil Abshor (Mahad Aly Al Fithrah, 2023)
The letters Alif and Alef are architectural masterpieces. Architecture is not only constructed to meet basic human needs. In a semiotic perspective, architecture is a text and is designed to be rich in philosophical values, so it is necessary to trace the meanings contained in it. This research is a literature, with a comparative inductive method. The approach is semiotic architecture. As a result, the Alif and Alef architectures are designed to be timeless so that the letter values can become a guideline that is firmly held by their users. Its extra-detailed design shows the sacredness of the letter. Apart from being the name of God, the letter is constructed as an icon of tahlil or tehlel monotheism that interprets the oneness of God and there is no God but Him. He is All Supreme and to Him man must submit, serve and hold on to His words. Its abstract qualities are the image of infinity and something indescribable. His intentions show that God is the Creator, can only be articulated through the wonders of His creations. The numerical value of one represents a beginning and the only path to be walked. One thousand is an infinity number that means everything comes from the One Dzat no one can feel high because God is Al-Mutakabbir. And among the ways of obtaining sprirituality is to neutralize lust.